Study on the influence of customers’ consumption intention in online food delivery service: Calorie label as the moderator variable - Huilin Yuan; Jue Wang (PLoS ONE, 2025)
Online food delivery (OFD) service, is a catering service model taking the Internet as the platform, where customers place orders online and enjoy offline delivery services. Customers’ attention on calorie labels when ordering food online is increasing with the increased health awareness in recent years. According to SERVQUAL model and Theory of Planned Behavior, this article constructed a structural equation model and then introduced calorie labels as a moderator variable. The data was obtained through a questionnaire survey, and a total of 222 valid responses from Chinese OFD service users were collected. Data was measured by SPSS software, and the structural equation model was analyzed by AMOS software. The results showed that food quality (path coefficient = 0.652, p < 0.001) and the kitchen photos (path coefficient = 0.849, p < 0.001) had greater influence on customers’ consumption intention. At the same time, calorie labels for OFD service stores have partly moderating effect on customers’ consumption intention. Regarding light-meal food and home-cooked food stores, calorie labels have a significantly positive moderating effect on the impact of OFD service quality on customers’ consumption intention. Regarding dessert and fried food stores, calorie labels have no moderating effect. The above researches put forward model reference and decision-making reference for improving OFD service quality and customers’ consumption intention and also contribute to the literature on OFD service by offering new insights into calorie labels.